Spousal interference and relational turbulence during the COVID-19 pandemic. Issue 5 (19th October 2020) - Knoster, Kevin; Howard, Heath A.; Goodboy, Alan K.; Dillow, Megan R.
ABSTRACT: Relational Turbulence Theory proposes that when romantic partners interrupt everyday routines in response to transitions, affective arousal will be heightened in the form of more intense emotions. The goal of this study was to test this theoretical logic in a married sample of 165 spouses during the initial peak of the COVID-19 pandemic (April, 2020). Participants completed an online survey measuring how often their spouse interfered with their daily routines, the negative emotions they experienced when interacting with their spouse, and how much turbulence they perceived in the marriage. Results of a parallel multiple mediation model provided support for the theory in the context of this global pandemic; anger and sadness toward the spouse independently mediated the effect of interference from that spouse on relational turbulence in the marriage.